From Childhood to Queerness: The Social Construction of Sexuality in Shyam Selvadurai’s Funny Boy - Joshi, Bhup Raj (Educational Journal, 2025)
This article examines the distinction between sex and sexuality through Shyam Selvadurai’s Funny Boy (1994). It situates Arjie’s coming-of-age struggle with his queer identity within the wider context of societal expectations and cultural narratives, emphasising how these forces construct sexuality in adulthood amid Sri Lanka’s escalating Sinhalese–Tamil conflict. While sex denotes the biological state of being male or female, the socialisation process crucially shapes one’s sexuality. The paper thus analyses sexuality as a socially constructed identity in Funny Boy, exploring how cultural norms and heteronormative discourses influence its formation and psychological implications for young adults. Employing qualitative textual analysis and secondary sources—books, journals, and research articles—the study draws on Michel Foucault’s The History of Sexuality, Judith Butler’s Gender Trouble, and Homi Bhabha’s The Location of Culture. Their theories of social construction, performativity, and hybridity suggest that society and culture play formative, rather than merely influential, roles in shaping identity.